PATHOPHYSIOLOGICALLY AND CLINICALLY SUBSTANTIATE CHANGES IN INTERLEUKIN DYNAMICS IN DIABETIC MACRO - AND MICROANGIOPATHIC WITH PATIENTS (Journal of Science-Innovative Research in Uzbekistan, 2025)
Determination of the effectiveness of ozone therapy and its pathomorphological properties with new pharmacological drugs for the treatment of purulent necrotic process of the foot. By studying the dynamics of anti-inflammatory cytokine levels: analysis of the need and possibility of immunoprotection by studying cytokine status in IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, TNF-α, INF-γ patients on the development and recurrence of purulent-necrotic processes of DFS.• Эрназаров, Х., Зохиров, А., Эргашев, У. Ю., & Исраилов, Р. (2022). Патоморфологическая картина жизненно важных органов при экспериментальной модели диабетической стопы.• Эрназаров, Х. И., Эргашев, У. Ю., Зоҳиров, А. Р., & Каримов, Х. Я. (2022). Эффективность использование препарата реоманнисол в лечении экспериментальной модели диабетической стопы.• Эргашев, У. Ю., & Зохиров, А. Р. (2023). Изучение патоморфологии печени при экспериментальном синдроме диабетической стопы.European Journal of Interdisciplinary Research and Development, 12, 27-31.• Зохиров, А. Р. (2023). Обоснование процессов эпителизации и регенерации при гнойно-некротических процессах нижних конечностей при сахарном диабете.Conferencea, 174-180.• Yusufjanovich, E. U., Rafiqovich, Z. A., & Tohirovich, G. B. (2023). Principles of studying liver morphology in experimental diabetic foot syndrome. World Bulletin of Public Health, 19, 63-65.• Yusufjanovich, E. U., Rafiqovich, Z. A., & Irsalievich, E. K. (2023). Assessment of the Process of Epithelialization After Complex Treatment of Diabetic Foot Syndrome. Texas Journal of Medical Science, 16, 19-23.• Yusufjanovich, E. U., & Rafiqovich, Z. A. (2023). Treatment of purulent-necrotic lesions of the lower extremities with modern drugs. Conferencea, 88-94.• Yusufjanovich, E. U., & Rafiqovich, Z. A. (2023). Evaluation of the lipid peroxidase index in diabetic complications. Conferencea, 68-73.• Rafiqovich, Z. A. (2023, February). Improving the detection of morphological changes in purulent wounds. In E Conference Zone(pp. 51-57).• Rafiqovich, Z. A. (2023). Study of the effect of lipid peroxidase analysis on the body in diabetic foot syndrome. Conferencea, 76-82.• Rafiqovich, Z. A. (2023). Observation of biochemical results in experimental diabetic foot syndrome. Conferencea, 181-188.• Rafiqovich, Z. A. (2023). Monitoring of the regeneration process in purulent-necrotic processes of the lower extremities. Conferencea, 189-194.• Rafiqovich, Z. A. (2023). Control of indicators of endotoxicosis in diabetic foot syndrome. Conferencea, 83-90.• Ergashev, U. Y., Zokhirov, A. R., & Minavarkhujaev, R. R. (2023). Study and treatment of changes in biochemical processes in complications of diabetes mellitus.• Ergashev, U. Y. (2022). Ernazarov Kh. I., Zohirov AR, Alzabni ID 2022. Complex Treatment of Experimental Model of Diabetic Foot Syndrome. American Journal of Medicine and Medical Sciences, 12(5), 471-480.• Эргашев, У. Ю., & Зохиров, А. Р. (2023). ИЗУЧЕНИЕ ПАТОМОРФОЛОГИИ ПЕЧЕНИ ПРИ ЭКСПЕРИМЕНТАЛЬНОМ СИНДРОМЕ ДИАБЕТИЧЕСКОЙ СТОПЫ.European Journal of Interdisciplinary Research and Development, 12, 27-31.• Yusufjanovich, E. U., Irisbaevich, M. G., Rafiqovich, Z. A., & Irsaliyevich, E. K. (2023). Evaluation of Effectiveness of Splenectomy in Chronic Leukemias. World Bulletin of Public Health, 19, 79-83.• Yusufjanovich, E. U., Rafiqovich, Z. A., & Tohirovich, G. B. (2023). PRINCIPLES OF STUDYING LIVER MORPHOLOGY IN EXPERIMENTAL DIABETIC FOOT SYNDROME. World Bulletin of Public Health, 19, 63-65.• Ergashev, U. Y., Minavarkhujayev, R. R., Gafurov, B. T., Malikov, N. M., Ortiqboyev, F. D., & Abdusalomov, B. A. (2022). Efficiency of Percutaneous Minimally Invasive Technologies in the Treatment of Patients with Obstructive Jaundice.• Моминов, А. Т., Маликов, Н. М., Якубов, Д. Р., & Абдусаломов, Б. А. (2022). Проблемы обезболивания в амбулаторной хирургии. European Journal of Interdisciplinary Research and Development, 10, 81-89.• Ergashev, U. Y., Abdusalomov, B. A., Minavarkhojayev, R. R., Ortiqboyev, F. D., & Malikov, N. M. (2023). Evaluation of the pathomorphology of regeneration in diabetic foot syndrome and determination of its dependence on biochemical processes. World Bulletin of Public Health, 19, 66-78.• Abdusalomov, B. A., & Rafiqovich, Z. A. (2023). THE MECHANISM OF ACTION OF THE GEL FORM OF COLLAGEN IN DIABETIC WOUNDS. International Journal of Medical Sciences And Clinical Research, 3(03), 96-103.• Ergashev, U. Y., Malikov, N. M., Yakubov, D. R., Abdusalomov, B. A., & Gafurov, B. T. (2023). Use of Collagen and Fibroblasts in Modern Medicine. Eurasian Research Bulletin, 17, 78-84.• Ergashev, U. Y., Mominov, A. T., Malikov, N. M., Yakubov, D. R., & Abdusalomov, B. A. (2023). MODERN APPROACH TO COMPLEX TREATMENT OF DIABETIC FOOT ULCERS. LITERATURE REVIEW.• Ergashev, U. Y., Abdusalomov, B. A., & Zohirov, A. R. (2023, May). Eksperimental diabetik tavon sindromida hayotiy muhim a’zolarning morfologik o’zgarishlarini nazorat qilish. /Material of International scientific and practical conference" An integrated approach to the treatment of complications of diabetes".• Abdusalomov, B. A. (2023). USE OF MODERN METHODS IN THE TREATMENT OF CHRONIC WOUNDS. Journal of Academic Research and Trends in Educational Sciences, 2(3), 213-220.• Abdusalomov, B. A. (2023). The Role of Collagen in The Mechanisms of Chronic Wound Healing for Diabetic Foot Syndrome. Texas Journal of Medical Science, 26, 86-94.• Ergashev, U. Y., Mominov, A. T., Malikov, N. M., Yakubov, D. R., & Abdusalomov, B. A. (2023). MODERN APPROACH TO COMPLEX TREATMENT OF DIABETIC FOOT ULCERS. (LITERATURE REVIEW).